1999
DOI: 10.1021/ja984384t
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculations on Disaccharide Mimics:  Studies of Molecular Geometries and Trans-O-glycosidic 3JCOCH and 3JCOCC Spin-Couplings

Abstract: Density functional theory (DFT) using the B3LYP functional and the split-valence 6-31G* basis set has been used to investigate the structures and conformations of four β-[1f4]-linked disaccharide mimics, 1-4. Systematic functional group substitution at sites near the glycosidic linkage was used to evaluate the effects of sterics and interresidue hydrogen bonding on the preferred glycosidic torsion angles φ and ψ. Using DFT-optimized geometries, the same hybrid functional, and a specially designed basis set, vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 89 publications
(167 citation statements)
references
References 34 publications
8
158
1
Order By: Relevance
“…However, since the Karplus relationships developed have different constants for their parametrization, the shape of the curve is altered somewhat and a slightly larger uncertainty must be used in the determined torsion angles. 18,20,21 In addition, one must not over-interpret data since 3 J(C,H) in 1 H-C-C-13 C-OH fragments have been shown to differ significantly (3.3 Hz) simply by changing the configuration of the hydroxyl group substituting the coupling pathway of interest. 22 One of the most useful applications of 3 J(C,H) in conjunction with Karplus relationships is, besides determination of stereochemistry, to reveal conformational trends in similar compounds, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…However, since the Karplus relationships developed have different constants for their parametrization, the shape of the curve is altered somewhat and a slightly larger uncertainty must be used in the determined torsion angles. 18,20,21 In addition, one must not over-interpret data since 3 J(C,H) in 1 H-C-C-13 C-OH fragments have been shown to differ significantly (3.3 Hz) simply by changing the configuration of the hydroxyl group substituting the coupling pathway of interest. 22 One of the most useful applications of 3 J(C,H) in conjunction with Karplus relationships is, besides determination of stereochemistry, to reveal conformational trends in similar compounds, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a shows that the MD-simulation achieved good to excellent fit to the experimental data. Out of four different Karplus equations for the glycosidic fragment HOCO in the literature, three 29,34,35 resulted in a satisfactory fit, whereas one 36 tended to over-estimate the coupling constants by 0.5-1.5 Hz. The over-estimation resulted presumably from the fact that carbohydrate mimics were used in the study and that the developed Karplus relation does not fully reflect conditions found in real carbohydrates.…”
Section: Molecular Modelingmentioning
confidence: 97%
“…Instead, the equation due to Wasylishen and Schaefer 20 was used. However, the expressions due to Tvaroska and Taravel 21 and Serianni 22 were also tried (they seemed particularly appropriate due to its previous application to carbohydrates and the 1,2-dioxy substitution in the compound under investigation), as was that of Aydin and Gunther 23 (see robustness discussion below). For 2-bond H-C couplings, the expression due to Contreras and Peralta was used.…”
Section: Resultsmentioning
confidence: 99%